Upaya Meningkatkan Hasil Belajar Shooting Sepakbola Melalui Permainan Shooting Colour Pada Siswa Kelas V SD - I Kadek Adi WIranata; I Ketut Semarayasa; I Wayan Muliarta; I Made Satyawan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
improve soccer shooting skills among fifth-grade students at Public Elementary School. The method used in this study was classroom action research, while the subjects were 30 fifth-grade students at Public Elementary School. The results of the study showed an increase in learning outcomes in soccer shooting with the Shooting Color game. Initial observations showed that only 7 students (23%) achieved the minimum passing grade. In cycle 1, there was a significant increase, with 13 students (43%) achieving the minimum passing grade. Meanwhile, in cycle 2, 25 students (83%) achieved the minimum passing grade. The results achieved in cycle 2 were in line with the target of 75% of students achieving the minimum passing grade. In this case, 83% of students achieved the minimum passing grade, so cycle III was not continued. The results also showed that there was an increase in student participation in soccer dribbling learning activities with color shooting games in two cycles, based on observations by collaborators. This was evident in the students' active participation. In conclusion, almost all students moved and participated actively. Soccer shooting learning with color shooting games was able to encourage students' creativity to be active during learning. Keywords: Playing Shooting Color, Learning Outcomes, Soccer, Shooting